High Intrinsic Barriers against Spin‐State Relaxation in Iron(II)‐Complex Solutions. Issue 3 (11th December 2012) - Stock, Philipp; Pędziński, Tomasz; Spintig, Nicole; Grohmann, Andreas; Hörner, Gerald
<x xml:space="preserve">Abstract</x> Slow relaxation: Exergonic high‐spin→low‐spin relaxation after photoexcitation has been found to be exceedingly slow in a class of iron(II) complexes with hexadentate imine ligands. The thermal activation barriers that arise between the quintet‐ and singlet‐spin manifolds are the highest ever recorded for spin crossover of isolated molecules in free solution (see figure).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>